2023
DOI: 10.3389/fenrg.2023.1197024
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent grid load forecasting based on BERT network model in low-carbon economy

Abstract: In recent years, the reduction of high carbon emissions has become a paramount objective for industries worldwide. In response, enterprises and industries are actively pursuing low-carbon transformations. Within this context, power systems have a pivotal role, as they are the primary drivers of national development. Efficient energy scheduling and utilization have therefore become critical concerns. The convergence of smart grid technology and artificial intelligence has propelled transformer load forecasting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(25 reference statements)
1
0
0
Order By: Relevance
“…The loss function of other algorithms finally exceeds 0.04, which shows that the breakwater wave prediction model based on BERT fusion with BiLSTM as proposed in this paper has a better convergence effect. This is related to the discovery of Tao et al [54]. Meanwhile, in the comparison accuracy and F1 value experiments, it was found that the prediction accuracy and F1 value of this research model algorithm reach 89.70% and 86.06%, respectively.…”
Section: Discussionsupporting
confidence: 69%
“…The loss function of other algorithms finally exceeds 0.04, which shows that the breakwater wave prediction model based on BERT fusion with BiLSTM as proposed in this paper has a better convergence effect. This is related to the discovery of Tao et al [54]. Meanwhile, in the comparison accuracy and F1 value experiments, it was found that the prediction accuracy and F1 value of this research model algorithm reach 89.70% and 86.06%, respectively.…”
Section: Discussionsupporting
confidence: 69%